Mechanical stability criterions of cubic Na2He up to 500 GPa - Daoud, Salah; Rekab-Djabri , Hamza (International Journal of Scientific World, 2023)
The Cauchy pressure Cp was usually used to explain the atomic bonding character in a compound, while the mechanical stability criterions are usually used to study the stability of the structure under external compression. Using the elastic constants reported recently by Zahidur Rahaman et al. in Chinese Journal of Physics, 56 (2018) 231-237, as well as different mathematical formula, we reported on the Cauchy violation and the generalized mechanical stability criterions of cubic Na2He compound under high hydrostatic compression from 100 GPa to 500 GPa. For pressures ranging from 100 to 500 GPa, all values of both Cauchy pressure Cp and the generalized mechanical stability criteria G are negative. In addition we calculated the Debye temperature θD of Na2He compound using Siethoff’s approach. The results obtained are slightly lower than those obtained from the Debye approach reported by Zahidur Rahaman et al.